Empowering SMES Performance through Digital Economy using Social Media and E-Wallet - Nurkholish Majid; Nuruni Ika Kusuma Wardhani; Zumrotul Fitriyah (Future Science, 2022)
This study aims to analyze the convenience and benefits of social media and E-wallets on the performance of SMEs. The study used quantitative analysis with SEM-PLS. The research sample was 30 SMES in Gunung Anyar District. The results showed that the ease and benefits of using social media and E-wallets were able to improve the performance of SMEs. The results of the study have implications for the use of social media and E-wallets as a form of the digital economy then increase economic growth, especially in MSMEs in Gunung Anyar and East Surabaya.